Vitamin D Receptor Gene Polymorphisms and Risk in Children with Recurrent Wheezy Chest among Babylon Province - Naser Z. Al-Jourany (Journal of Global Pharma Technology, 2018)
Introduction: wheezing is continuous whistling happen from the chest in breathing; early childhood wheezing may develop later to asthma, this study aimed to make a genetic study to show the relationship between recurrence of wheezing, and polymorphism in vitamin D receptor. This has not been explored in Iraqi settings widely.  Aim: Present study investigated the association between VDR gene BsmI single nucleotide polymorphisms and recurrent wheeze in patients with a recurrent wheezy chest in Babylon children. Materials and Methods: Ninety patients with recurrent wheezy chest and ninety apparently healthy children as a control in Hilla City/Iraq were enrolled in this study. A questionnaire was used to obtain information. Estimation of VDR gene BsmI single nucleotide polymorphism was done using the PCR-RFLP method. Standard statistical tools were used, p-value <0.05 was considered to be statistically significant. And p-value <0.001 was considered to be statistically a highly significant SPSS software version 20.0 was used.  Results: The genotype and allele distribution of the VDR BsmI A/G SNP showed a significant difference between cases and controls with (p-value < 0.001).  Conclusion: The study concluded that BsmI gene polymorphism of vitamin D receptor associated with a recurrent wheezy chest in children beyond 5 years in Babylon province. Moreover, this study, conclude some risk factors that related to recurrent wheezing that the male gender is more affected and the children who breastfeed for less than six months is more vulnerable for wheezing and the family history of allergic rhinitis and maternal asthma also play role in patient wheezing.Keywords: Recurrent wheezing, Vitamin D receptor, SNPs, Babylon province.